Celebrating Adaptive Delivery: A View from the Frontline in Myanmar - Barnes, Katrina; Lonsdale, Jane (IDS Working Paper, 2023)
The conversation on adaptive management has grown fast amongst development actors. These conversations often focus on designing, commissioning, and managing large-scale development programmes. Exactly how this impacts the frontline, the implementers, and day-to-day project delivery is still being debated. Yet, perspectives drawn directly from practice are often largely missing within these debates. This paper is written by two development practitioners. Through this paper, we reflect on the difference between adaptive management and adaptive delivery, and how this interacts with risk and aid accountability, particularly in contexts of fragility. Drawing on examples of Oxfam in Myanmar work and our personal insights in relation to delivering programming across humanitarian, peace-building, and development, we suggest that in complex, conflict-affected, and highly political environments adaptive delivery already happens far more regularly than is currently recognised, as a necessity to get activities delivered. However, it happens despite the system, not because of it, and is therefore often hidden and carried out ‘under the radar’ rather than celebrated as a success in difficult environments. This paper was written in 2019, before the military seized control of Myanmar in February 2021. Whilst it draws on examples from pre-2021 Myanmar to illustrate real life cases, it is a contribution to a broader global debate on adaptive management in practice, specifically in fragile contexts. This is not specifically aimed at practitioners working in Myanmar at present, who are now working in a protracted crisis. This paper makes tangible recommendations on steps that donors, international non-governmental organisations, local staff, and partners could take to promote a system of encouraging and celebrating adaptability in programme delivery in fragile contexts.

Applying Adaptive Management in a Fragile Context – Case Study - Lonsdale, Jane; Green, Duncan; Robertson, Kelly (DT Global, 2023)
DT Global is proud to introduce our new Guidance Note: Practical Introduction to Adaptive Management There is a growing consensus around adaptive management as an effective (even necessary) approach when programs are tackling complex development problems. While there is no standard definition of adaptive management, there is general agreement that such programs need to routinely engage with and respond to program context; constantly test what works in that context; and adjust approaches, plans, and activities based on continuous learning. However, there remains a more limited body of evidence about what this looks like in practice—the enabling conditions, systems, resourcing, skills, and attitudes to effectively operationalise adaptive management. There is also limited guidance around when adaptive management is required, and to what extent—both critical and often overlooked considerations when planning for successful adaptive management. This Guidance Note draws together lessons and good practice in adaptive management from across DT Global’s diverse portfolio of donor-funded programs. It outlines our conceptual framework for adaptive management, with practical guidance on how it can be applied by our program teams. It is also designed to help our teams distinguish adaptive management from good (non adaptive) project management, consider when adaptive management is most useful on a program, and how adaptive a program (or part of a program) should be.

Adaptive Programming and going with the grain: IMAGINE's new water governance model in Goma, DRC - Kirk, Tom; Green, Duncan; Stys, Patrycja; Mosquera, Tom (Development Policy Review, 2023)
Motivation This paper explores adaptive approaches to development programmes that aim at improving service provision in underperforming sectors in fragile and conflict affected states (FCAS). It does this through a case study of the Integrated Maji Infrastructure and Governance Initiative for eastern Democratic Republic of the Congo's (IMAGINE) public-private partnership model for water provision. Purpose The processes and decisions that culminated in IMAGINE's model emphasize the need for programming that is culturally and politically aware, responsive to events, learns in real-time, is entrepreneurial, and works with the grain of local institutions to support change. Detailed case studies of such ways of working are crucial for programmes that seek to challenge and reform the status quo in FCAS. Methods and approach The paper is based on 42 semi-structured interviews conducted in the summers of 2019 and 2020. They reflect the broad spectrum of actors – individuals, public authorities, and organisations – involved in IMAGINE's evolution. Findings The narrative focuses on IMAGINE's attempts to professionalise and commercialise Goma's water sector. It shows how as IMAGINE repeatedly adapted to ground realities, it took on the characteristics of a public authority, thereby, engendering backlashes that threated its longer-term goals. However, by revisiting its initial values and logics it was able to get things done and achieve it aims. Policy implications IMAGINE's story suggests that adaptive programmes should put politically savvy local development professionals in key positions and enable them to carefully construct coalitions of allies across the systems they aim to disrupt. This may also require them to revisit and adapt their initial ideas, guiding principles and values as greater understandings of development problems are gained. A pubic authorities lens, attuned to the logics programmes seek to address and introduce to FCAS, may help analysts to foreground the implications of such adaptations.

Building a team culture for Adaptive Management in MSD: 5 Strategies MEL Managers Say Work - Gover, Dun; Nasution, Zulka; Okutu, David; Bolder, Meghan; Henao, Lina (MSD in MEL Brief, 2023)
Keywords: Bolder Meghan; Gover Dun; Henao Lina; Nasution Zulka; Okutu David

Systems-aware social accountability: Harnessing Practitioner Insights for More Responsive Governance - Guerzovich, Florencia (Pact, 2023)
The framework’s four principles, described below, are not exclusive to social accountability interventions; for example, Pact has published tools on how to use political economy analysis or integrate adaptive management principles into programming. Rather, the principles highlight how – by including the right combination of mindsets, management approaches, analytic approaches and tools – practitioners can develop and apply a deep understanding of a system to improve relationships within it, in support of greater accountability and improved service delivery. - Use a Holistic Lens - Recognize that there is always a system; understand and engage with it​: Developing a strong understanding of the system in which a project works and effectively integrating this knowledge into implementation increases the chances that local actors will sustain the interventions. - Right Fit the Approach​ - Equipped with a holistic understanding of the context, teams identify where they have a comparative advantage in a specific system. In other words, they identify where their resources, expertise and partners have the greatest potential for impact, then set realistic targets that they revise periodically. -Orchestrate Across The System -​ Practitioners take a networked, rather than a top-down, approach to capitalize on their convening power and maximize opportunity to facilitate the most-promising alignments across and within their projects, portfolios and systems. Orchestrators use their individual power, relationships and insight into the local system to enable, not impose, promising interactions and mitigate the risks of damaging ones. - Manage Adaptively - Monitor, evaluate and reflect on emerging patterns of data, evidence and learning to inform decision-making within and, equally importantly, across project cycles. Where possible, practitioners should consider how to use short-term projects to play a long-term game by linking new projects to the lessons and results of their predecessors and ensuring that they are responsive to the evolving context, particularly opportunities, limits and risks.

Adaptive Evaluation: A Complexity-based approach to Systematic Learning for Innovation and Scaling in Development - Gokhale, Siddhant; Walton, Michael (CID Faculty Working Paper, 2023)
Nearly all challenges in international development tend to be complex because they depend on constantly evolving human behaviour, systems, and contexts, involving multiple actors, entities, and processes. As a result, both the discovery and scaling of innovations to address challenges in development often involve changes in system behaviour or even system-level transformation. This is rarely a linear process over time and can result in unexpected outcomes. Existing evaluation techniques commonly used in international development, including Randomized Control Trials (RCT) and quasi-experimental methods, are good at assessing specific effects of interventions but are not designed for the change processes inherent to innovation and scaling within a system. There is a need to reconstruct how we use existing measurement tools, techniques, and methodologies so that they capture the complexity of the environment in which an intervention or change occurs. We introduce Adaptive Evaluation, designed to learn at various levels of complexity while supporting the transformation needed to foster sustainable change. An Adaptive Evaluation uses three main approaches to work with complex questions—systems diagnosis, theorybased assessment of change processes, and iterative designs. An Adaptive Evaluation typically builds hypotheses from field-based interactions, emphasizes learning over testing, advocates open-mindedness with techniques, and appreciates the value of dialogue and participation in navigating complex processes. It can use RCT or similar techniques to analyse specific processes within a system or a development cycle, but these are embedded in a broader approach to assessment and interpretation. It is designed to be flexible and adjust to shifting contexts. Finally, an Adaptive Evaluation can be applied at any stage in a complex intervention's lifecycle, from the interpretation of the system and change processes to rapid experimentation, prototyping, and testing of select interventions, and then adaptation to different settings for impact at scale. This paper provides the theoretical basis for an Adaptive Evaluation—the main approaches, core ideology, process, and applications.

Enhancing partner and system-level learning: 8 Tips from MEL Managers - Gover, Dun; Nasution, Zulka; Okutu, David; Bolder, Meghan; Henao, Lina (MSD in MEL Brief, 2023)
Effective learning is a key driver of market systems change, with the potential to enhance system competitiveness, resilience, and inclusiveness. Shifting the Locus of Learning: Catalyzing Private Sector Learning to Drive Systemic Change recently outlined a rationale for enhancing the scale and quality of learning in a system and identifying 10 strategies programs can contextualize to catalyze learning. These strategies are also backed with robust examples from 13 programs doing this work across 11 countries. To deepen insights on what MSD Monitoring, Evaluation and Learning (MEL) Managers have experienced in putting several of those strategies into practice, the Feed the Future Market Systems and Partnerships (MSP) Activity convened a series of peer discussions as part of a larger initiative (see Figure 1). This brief shares the collective learning and experience on this topic of three senior MEL Managers who were interested in and had experience with this topic. The group represented full-time, program-based MEL Leads working on MSD programs funded by USAID and DFAT, based in Fiji, Albania, and Kosovo working for Adam Smith International, SwissContact, and DT Global, respectively. From those discussions, this paper synthesizes eight tips from MEL Managers for practically enhancing partner and system-level learning: 1. Identify the right decision-maker(s) at potential partners. 2. Use a co-creation process to identify learning opportunities. 3. Use diagnostics and assessments to strengthen partner and system capacity for actionable learning. 4. Use a phased capacity strengthening process tied to behavior change. 5. Measure partners’ continued investment in and use of learning—not the continuation of specific learning activities. 6. Work with sector-level institutions for scale but be aware of risks. 7. Leverage informal communities of practice to share learning. 8. Use the right terminology to talk about partner and system-focused learning.

Anatomy of Social Accountability 3.0: A working framework for moving forward - Guerzovich, Florencia; Aston, Tom (Florianopolis, SC, Brazil: Grupo Politeia, ESAG, University of the State of Santa Catarina and act4delivery, 2023)
This note presents the key components of a potential next generation of social accountability programming. The key aspects outlined emerge from a review of over 150 cases as well as tacit knowledge from dozens of practitioners (Guerzovich and Aston, 2023).The main thread of social accountability 3.0 and what distinguishes it from previous generations is a focus on its contribution towards more responsive systems and accountable social contracts. In particular, social accountability should be considered as an operational means to rework social contracts.Over the last two decades, the field has been defined by a supposed dichotomy between minimalist (i.e., “widget” based) approach or a maximalist (“go big or go home”) approaches. Yet, most practice sits somewhere between these extremes. The paper presents various options derived from practice; practitioners should choose whichever best fits their own particular circumstances.Those hoping to improve and expand their practice with a systems-lens may benefit from considering how they approach the key elements of social accountability 3.0.
Keywords: accountability; development; responsiveness; social accountability; social contract; systems

Laying the Foundations for Impact: Lessons from the GCRF Evaluation - Vogel, Isabel; Barnett, Chris (The European Journal of Development Research, 2023)
Research for development (R4D) aims to make a tangible difference to development challenges, but these effects typically take years to emerge. Evaluation (especially impact evaluation) often takes place before there is evidence of development impact. In this paper, we focus on opportunities for assessing the potential for impact at earlier stages in the research and innovation process. We argue that such a focus can help research programme managers and evaluators learn about the pre-conditions for impact and adjust accordingly. Using the Global Challenges Research Fund (GCRF) as a large-scale case of R4D evaluation, we identify and explore some of the building blocks that can increase impact potential. Guided by GCRF’s theory of change, we explore emerging evidence that highlights the importance of ways of working that supports positioning for impact. We conclude by drawing out a unifying construct around standards of development excellence; to sit alongside notions of scientific excellence for research intended to have an impact. Standards can help programme managers, researchers and evaluators learn and adapt to increase the likelihood of impact.

How are Research for Development Programmes Implementing and Evaluating Equitable Partnerships to Address Power Asymmetries? - Snijder, Mieke; Steege, Rosie; Callander, Michelle; Wahome, Michel; Rahman, M. Feisal; Apgar, Marina; Theobald, Sally; Bracken, Louise J.; Dean, Laura; Mansaray, Bintu; Saligram, Prasanna; Garimella, Surekha; et al. (The European Journal of Development Research, 2023)
The complexity of issues addressed by research for development (R4D) requires collaborations between partners from a range of disciplines and cultural contexts. Power asymmetries within such partnerships may obstruct the fair distribution of resources, responsibilities and benefits across all partners. This paper presents a cross-case analysis of five R4D partnership evaluations, their methods and how they unearthed and addressed power asymmetries. It contributes to the field of R4D partnership evaluations by detailing approaches and methods employed to evaluate these partnerships. Theory-based evaluations deepened understandings of how equitable partnerships contribute to R4D generating impact and centring the relational side of R4D. Participatory approaches that involved all partners in developing and evaluating partnership principles ensured contextually appropriate definitions and a focus on what partners value.

How Big Things Get Done: The Surprising Factors Behind Every Successful Project, from Home Renovations to Space Exploration - Flyvbjerg, Bent; Gardner, Dan (Macmillan, 2023)
World expert Bent Flyvbjerg and bestselling author Dan Gardner reveal the secrets to successfully planning and delivering ambitious projects on any scale.Nothing is more inspiring than a big vision that becomes a triumphant new reality. Think of how Apple’s iPod went from a project with a single employee to an enormously successful product launch in eleven months. But such successes are the exception. Consider how London’s Crossrail project delivered five years late and billions over budget. More modest endeavours, whether launching a small business, organizing a conference, or just finishing a work project on time, also commonly fail. Why?Understanding what distinguishes the triumphs from the failures has been the life’s work of Oxford professor Bent Flyvbjerg. In How Big Things Get Done, he identifies the errors that lead projects to fail, and the research-based principles that will make yours succeed:- Understand your odds. If you don’t know them, you won’t win.- Plan slow, act fast. Getting to the action quick feels right. But it’s wrong.- Think right to left. Start with your goal, then identify the steps to get there.- Find your Lego. Big is best built from small.- Master the unknown unknowns. Most think they can’t, so they fail. Flyvbjerg shows how you can.Full of vivid examples ranging from the building of the Sydney Opera House to the making of the latest Pixar blockbusters, How Big Things Get Done reveals how to get any ambitious project done – on time and on budget.

How to Build Movements with Cyclical Patterns in Mind - Non Profit News | Nonprofit Quarterly - Algoso, Dave; Guerzovich, Florencia; Gattoni, Soledad (Nonprofit Quarterly, 2023)
The world changes too much for anyone who is invested in social change work to imagine that this work is linear and predictable. Opportunities come and go, whether caused by a pandemic or political shifts. This much most social movement leaders and activists intuitively understand. But what can be done with this realization? How might movement groups better prepare for moments of opportunity? We want to explore how we can create the changes we want to see by responding to the changes that are outside our control.

The Art of Scaling Deep - Research in Summary - Fraser, Tatiana (The Systems Sanctuary, 2023)
Over the last 15 years the concept of scale has become a foundational part of the apparatus of the social and environmental change sector. A business mindset of growth has been seamlessly transferred to the social and environmental problems we are collectively trying to shift in the world. Scaling up, (influencing policy) has been considered the strategic pathway to systems change. Scaling out (spreading new models) is seen as a pathway to success. The allure of these scaling theories lies, in part, in their tangibility, and the easy way in which they can be measured. However this focus on growth has shifted our attention away from a series of messy truths. Sometimes bigger isn't better. Endless growth is not sustainable and our urgency to try to fix the problem and seek solutions may be part of the crisis we are in. One unintended consequence of this has been that another type of scale has been devalued and as a result, under-resourced. It’s a scale that values the slow steady work of deepening relationships. It recognizes the significance of context, building connections that bridge diverse communities and it prioritizes inner work and healing as integral components of the scaling process. We call this type of scale ‘Scaling Deep’ and we believe that adequately supporting it, and funding it, holds the greatest potential for long lasting systemic change. The purpose of this research has been to delve deeper into the art and craft of Scaling Deep. Ultimately, our goal is for it to become firmly ingrained within the recognized realm of social change, alongside the well-established concepts of scaling up and scaling out. We want practitioners who are Scaling Deep to be able to harness the wisdom and power of this work and to talk about it openly, with confidence and credibility. We want understanding of this approach to flourish and evolve and for it to be appropriately celebrated and supported. We want decision-makers to be informed and inspired by the principles and practices of scaling deep. For it to be embedded in theories of change as an essential component of decision-making processes within the wider change discourse. Importantly we want leaders who are Scaling Deep to have access to sufficient resources and to receive the care from the field that they need to thrive. We would like to see organisations that have the power to invest, to align their efforts with the profound impact that scaling deep aspires to cultivate in the world. Before we begin, let us be crystal clear. We are not opposed to scaling up and out as strategies for change. Innovation and scaling what is working is part of how we evolve as humanity. As social entrepreneurs ourselves, we have both done this twice over. We value it and we know it’s important. We recognize these are strategies for creating widespread impact and effecting positive change. Our intention here is not to dismiss or undermine the value of scaling up and out, but rather to encourage a broader and more holistic perspective that includes other dimensions of scale. There is a need to understand how the different scaling approaches can work together, rather than seeing them as hierarchical and disconnected. Our ultimate goal is to equip the change sector with a more inclusive, expansive, and powerful approach to tackling the myriad challenges we face, by exploring the potential of Scaling Deep as a transformational strategy for systems change.

Theory of Change in complex Research for Development programmes: challenges and solutions from the Global Challenges Research Fund - Chapman, Sarah; Boodhoo, Adiilah; Duffy, Carren; Goodman, Suki; Michalopoulou, Maria (The European Journal of Development Research, 2023)
The United Kingdom Research and Innovation (UKRI) Global Challenges Research Fund (GCRF) aimed to address global challenges to achieve the United Nations (UN) Sustainable Development Goals through 12 interdisciplinary research hubs. This research documents key lessons learned around working with Theory of Change (ToC) to guide Monitoring, Evaluation and Learning (MEL) within these complex research for development hubs. Interviews and document reviews were conducted in ten of the research hubs. The results revealed that only one hub invested in an explicit visual system mapping approach, and that funder timelines, budget constraints and issues with capacity and expertise limited the application of these approaches across all hubs. In contrast, many hubs attempted to deal with visual complexity by means of ether constructing multiple, nested ToCs, or a conscious simplification of complexity through reducing their ToC towards a straightforward and uncomplicated chain model or spherical model. While the former approach had some value, most hubs struggled to find capacity to support the full articulation of nested ToCs. In contrast, the latter approach resulted in ToCs which lacked detail or mechanism articulation, but which nevertheless were often ‘fit for purpose’ in ensuring effective communication and coherence across diverse stakeholders and sub-projects. We conclude that in instances where the reporting, funding and management cycles of complex research for development programmes cannot be adapted to properly support learning-based approaches to ToC development, imposing simplicity in the ToC might be fit for purpose. This might also be preferable to more complex visual approaches that are only partially realised.

Participation for Humanitarian Innovation - Toolkit - Smith, Amy; Thompson, Martha; Saida Benhayoune; Crespo Cardona, Omar (Elrha, 2023)
A resource designed to help organisations, teams and individuals manage innovation journeys responsibly and successfully. We have partnered with MIT D-Lab to develop a new resource to drive greater diversity and inclusion within project design and implementation. The Participation for Humanitarian Innovation (PfHI) toolkit sets out a robust approach to setting expectations for and monitoring the degree of participation within research and innovation projects for, with, and by people affected by crisis. The PfHI toolkit is composed of five tools: Opportunity Adviser: Identify and prioritise the desired benefits of participation while weighing the potential barriers. Participation Matrix: Agree on the precise degree of participation to target at a given project stage. Resource Navigator: Select tools and processes to address the needs of stakeholders, the project objectives and context. Quality Guidance: Ensure engagements are delivered to the highest standard. Assessment Matrix: Collectively evaluate the degree of participation achieved during an activity or project phase, learn and adapt. By applying these tools before, during and after a research and/or innovation project, implementors can ensure that stakeholders/end-users are included and participating at the highest possible degree. We encourage users of the PfHI toolkit to consider how else to integrate the tools into existing practices. For instance, the Evaluation Matrix could be used to supplement existing MEAL activities to: Establish baselines to measure changes in participation over time. Track the degree of participation/engagement of stakeholders. Regularly assess the degree of participation. Seek feedback from participants about the degree of their participation. Monitor the progress of activities related to stakeholder engagement. Our Participation for Humanitarian Innovation toolkit represents our ongoing commitment to responsible research and innovation across our portfolio of grants and for the humanitarian sector more broadly. We hope you will consider downloading and using the toolkit on your next project.

Participation for Humanitarian Innovation - Background Paper - Smith, Amy; Thompson, Martha; Saida Benhayoune; Crespo Cardona, Omar (Elrha, 2023)
A resource designed to help organisations, teams and individuals manage innovation journeys responsibly and successfully. We have partnered with MIT D-Lab to develop a new resource to drive greater diversity and inclusion within project design and implementation. The Participation for Humanitarian Innovation (PfHI) toolkit sets out a robust approach to setting expectations for and monitoring the degree of participation within research and innovation projects for, with, and by people affected by crisis. The PfHI toolkit is composed of five tools: Opportunity Adviser: Identify and prioritise the desired benefits of participation while weighing the potential barriers. Participation Matrix: Agree on the precise degree of participation to target at a given project stage. Resource Navigator: Select tools and processes to address the needs of stakeholders, the project objectives and context. Quality Guidance: Ensure engagements are delivered to the highest standard. Assessment Matrix: Collectively evaluate the degree of participation achieved during an activity or project phase, learn and adapt. By applying these tools before, during and after a research and/or innovation project, implementors can ensure that stakeholders/end-users are included and participating at the highest possible degree. We encourage users of the PfHI toolkit to consider how else to integrate the tools into existing practices. For instance, the Evaluation Matrix could be used to supplement existing MEAL activities to: Establish baselines to measure changes in participation over time. Track the degree of participation/engagement of stakeholders. Regularly assess the degree of participation. Seek feedback from participants about the degree of their participation. Monitor the progress of activities related to stakeholder engagement. Our Participation for Humanitarian Innovation toolkit represents our ongoing commitment to responsible research and innovation across our portfolio of grants and for the humanitarian sector more broadly. We hope you will consider downloading and using the toolkit on your next project.